Canada : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper assesses the long-term fiscal position of Canada. Simulations based on current tax and spending policies suggest that the fiscal position will remain favorable until well into the middle of the century, and relatively modest adjustments would be required to make these policies sustainable in the long term. The analysis also illustrates that these conclusions could be easily overturned if pressures to spend the planning surpluses that are expected to emerge in coming years are not resisted, and if measures are not put in place to contain the cost of health care.